GAMBARAN PELAKSANAAN PEMBERIAN KAPSUL VITAMIN A PADA IBU NIFAS (STUDI DI WILAYAH KERJA PUSKESMAS KALIBAWANG KABUPATEN WONOSOBO) (Unnes Journal of Public Health, 2015)
The International Vitamin A Consultative Group (IVACG) recommend that all post partum mother should receive two capsules of vitamin A. First capsule given at least one day apart as soon after delivery as possible and not more than 6 weeks later. This study was carried out to know Implementation Overview of Vitamin A Capsules Supplementation For Post-Partum Mothers In The Working Area of Kalibawang Centre of Public Health, Wonosobo District. This was a qualitative research. Informants selected using purposive sampling. The informants were 21 people. There are 3 village midwifes, 9 cadres (volunteer workers in the village) and 9 postpartum mothers. Data items were collected by indepth interview, observation and documentation methods. Data items were analyzed by data collection, data reduction, data presentation and data verification.The result showed that knowledge of the cadres and postpartum mothers still low, availability of vitamin A capsules in village midwife dependent in availability of vitamin A capsules in public health center and health departement, the role of village midwife is still not performed optimally yet and the role of cadres not implement